2019
DOI: 10.1108/jepp-03-2019-102
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial growth in elite team sport SME’s in Finland

Abstract: Purpose Entrepreneurship in the sport sector has become an important discussion topic amongst public policymakers in Finland, and the interface between entrepreneurial sport companies and the public sector is crucial in the development of sport entrepreneurship. The purpose of this paper is to discuss the entrepreneurial growth of two elite team sport companies in Finland by describing the entrepreneurial characteristics and organizational development affecting their growth. This paper aims at giving new insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…Therefore, from a sport entrepreneurship focus point of view, the study agrees with the network aspect of sport entrepreneurship. This research complements research by Ahonen (2019) who found that sport entrepreneurship is dependent on a favourable operating environment and on policy-makers’ capability but extends it to reveal the impact of family roles.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, from a sport entrepreneurship focus point of view, the study agrees with the network aspect of sport entrepreneurship. This research complements research by Ahonen (2019) who found that sport entrepreneurship is dependent on a favourable operating environment and on policy-makers’ capability but extends it to reveal the impact of family roles.…”
Section: Discussionsupporting
confidence: 66%
“…Besides, the concepts developed around international entrepreneurship emphasises the dynamism, recognition of opportunities, and value creation of business across international borders (Baier-Fuentes et al, 2019;Crespo and Aurélio, 2020); elements that are notably present in the international expansion of the team-sport leagues. Furthermore, some authors highlight that we find certain peculiarities in sport that are similar to entrepreneurship (Ahonen, 2019;Ratten and Tajeddini, 2019).…”
Section: Introductionmentioning
confidence: 62%
“…The main differentiating characteristics that have been brought up in the previous study as having implications for a sports equipment firm's internal management processes are winning performance (defeating opponent and winning trophies) and social value (Ahonen, 2019). Beech and Chadwick (2013) pointed out that sports equipment business has a battle in two areas: on the sport and in business.…”
Section: Special Characteristic Of Sports Equipment Firmsmentioning
confidence: 98%
“…The thought that the sports equipment business is unique from other manufacturing businesses is shown in the dissimilarity of forms by numerous scholars in previous studies. Especially, sports equipment firms are unique and different from other types of firms which various studies do so in more precise ways (Ahonen, 2019;Beech & Chadwick, 2013;Hoye, Nicholson, & Smith, 2008;Mangan, 2000;Slack, 1996).…”
Section: Special Characteristic Of Sports Equipment Firmsmentioning
confidence: 99%
See 1 more Smart Citation